Eliminating Preoperative Lymphoscintigraphy in Extremity Melanomas. Issue 3 (March 2018) - McGregor, Andrew; Pavri, Sabrina N.; Kim, Samuel; Xu, Xiaolu; Narayan, Deepak
Abstract : Background: Preoperative lymphoscintigraphy (LSG) is an imaging procedure routinely used to identify the draining nodal basin in melanomas. At our institute, we have traditionally performed preoperative LSG followed by intraoperative LSG for logistical and evaluative reasons. We sought to determine if preoperative LSG could be safely eliminated in the treatment of extremity melanomas, which exhibit consistent and predictable lymphatic drainage patterns. Methods: We reviewed the Yale Melanoma Registry 1308012545 for cutaneous extremity melanomas treated at our institution. From this registry, we calculated the incidence of atypical lymph node drainage patterns outside the axillary and inguinal regions. Based on these data, we eliminated preoperative LSG in 21 cases (8 upper extremities and 13 lower extremities). Additionally, we calculated the potential hospital charge reduction of forgoing preoperative LSG. Results: Upper and lower extremity melanomas treated at our institution exhibited atypical lymph node drainage at a rate of 3.4% and 2.0%, respectively. The sites of atypical drainage were to the epitrochlear and popliteal regions. In all 21 cases where preoperative LSG was eliminated, we were able to correctly identify the sentinel lymph node. The potential hospital charge reduction of forgoing preoperative LSG totaled 2, 393. Conclusions: Preoperative LSG can be safely eliminated in the management of upper and lower extremity melanomas. Exceptions may be considered for primary lesions of the posterior calf, ankle, and heel as well as for patients with history of prior surgery or radiation. Forgoing preoperative LSG results in a hospital charge reduction of 2, 393 and provides additional benefits to the patient. Ultimately, there is potential for significant charge reduction if applied across health care systems.